The development of the peripheral nervous system in the fruitfly Drosophila - Bellen, Hugo (Henry Stewart Talks, 2008)
The development of the peripheral nervous system in Drosophila serves as a model system, Isolate and characterize new genes and proteins that play a key role in neurogenesis and neural differentiation in most organisms
Reviewed at 2018/05/31